Struktura slovenskih spletnih strani - Dogša, Tomaž (Uporabna informatika (Ljubljana), 2000)
In this paper the results of web analysis that was aimed to explore the stucture and dynamics og web documents. 100 randomly chosen Slovenian web documents were analysed in the year 1998 and 2000. The results have been compared with those of USA and Germany.
Keywords: internet; Slovenija; spletne strani